دور الوسائل التعليمية في اكتساب مهارات القراءة و الكتابة في المرحلة الابتدائية - بلبكاي, جمال (جامعة الوادي - University of Eloued, 2017)
للوسائل التعليمية دور هام في العملية التعليمية، حيث يستطيع من خلالها المعلّم أن يجعل حصصه الدّراسيّة ناجحة محققة الأهداف، وأن ينقل جوّ الحصّة من الرّتابة و الخمول إلى جوّ من التفاعل و الحركة و رغبة المتعلم في التعاطي مع الدّرس راغباً فيه لا مكرهاً عليه ،مما يزيد في تشوّقه لطلب العلم و الإقبال على المعرفة، وذلك هو الهدف الأسمى لعملية التعليم والتعلّم لكلّ منظومة تربويّة. كما أن فاعلية تدريس مهارتي القراءة والكتابة ترتبط في شطر كبير منها بتنويع الوسائل التعليمية و استثمار الوسائل الحديثة التي أوجدتها التكنولوجيا المعاصرة، لأن وضعيات التعليم والتعلم و أكثرها نجاعةً هي التي تنوّع في استخدام تلك الوسائل، ولهذا فالدّراسة Teaching tools have a significant role in the educational process through which the teacher can make his classes successful, transfer the atmosphere from monotony and passiveness to the atmosphere of interaction and vividness, and make the learner willing to take his lessons not obliged to. In this respect, the teacher instills in the learner enthusiasm and a thirst for knowledge, and consequently this is the ultimate goal of the process of teaching and learning for each educational system. The effectiveness of teaching reading and writing skills is connected in large part to the diversity of the teaching tools and the investment of modern means created by contemporary technology because the most successful teaching and learning modes are those which diversify in the use of those means. Therefore, this study deals with the role of teaching tools in acquiring reading and writing skills in primary education
مقال في مجلة السراج في التربية وقضايا المجتمع بجامعة الوادي
Keywords: الوسائل التعليمية، المهارات، القراءة، الكتابة، التعليم الابتدائي; Teaching Tools, Skills, Reading, Writing, Primary Education.